Arabic Lexicons in The Contemporary Legal System - Tb Ahmad Mahdi; Atu Karomah; Haryana; Muhamad Lutfhi Ramadhan (Institut Agama Islam Negeri Palopo, 2024)
This article explores the complexities and challenges of understanding and translating Arabic terms in the context of contemporary legal systems. The Arabic language, which is rich in nuances and has a deep Islamic legal heritage, plays a central role in shaping legal foundations. Key terms such as hudud, ta'zir and faraid take centre stage, with an emphasis on the need for a deep understanding of culture and history to ensure accurate interpretation of the law. The article identifies key challenges, including contextual differences and terminological discrepancies between countries, and details the impact of misunderstanding Arabic on the fair enforcement and harmonisation of international law. By inviting in-depth reflection, the article highlights the importance of a cautious approach and interdisciplinary collaboration to ensure that Arabic is not only correctly translated, but also contextually understood in an increasingly complex and cross-border connected contemporary law.